Studi Penambahan Sari Daun Bayam Hijau Amaranthus Tricolor Terhadap Brownis Kukus - Ningsi, Fahriya; Fatmawati, Fatmawati; Halik , Abdul (PALLANGGA: Journal of Agriculture Science and Research, 2025)
Brownies are one of the bakery products that are very popular and commonly consumed by people in Indonesia. Spinach (Amaranthus) is considered the king of vegetables because its nutritional content contains vitamins A, B, and C, in addition spinach contains important mineral salts such as calcium, phosphorus, and iron. This study aims to determine the effect of adding green spinach leaf juice to steamed brownies and to determine the best concentration of green spinach leaf juice in steamed brownies for organoleptic tests of color, aroma, taste, texture and water content and ash content tests. The research treatment was the addition of green spinach leaf juice (0%, 2%, 4%, and 6%). Data analysis used a completely randomized design (CRD) method with 4 treatment levels and 3 replications. The best result of adding green spinach leaf extract to making steamed brownies was treatment B2 (4%) green spinach leaf extract, seen from the results of water content (41.27%), ash content (0.59%), organoleptic test of color 3.97 (like), aroma 3.84 (like), taste 4.03 (like), and texture 4 (like). Brownis adalah salah satu produk bakery yang sudah sangat populer dan umum dikonsumsi oleh masyarakat di Indonesia. Bayam (Amaranthus) dianggap sebagai raja sayuran karena kandungan gizinya mengandung vitamin A, B, dan C, selain itu bayam mengandung garam-garam mineral yang penting seperti kalsium, fosfor, dan zat besi. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan sari daun bayam hijau terhadap brownis kukus dan mengetahui konsentrasi terbaik sari daun bayam hijau pada brownis kukus terhadap uji organoleptik warna, aroma, cita rasa, tekstur dan uji kadar air dan kadar abu. Perlakuan penelitian yaitu dengan penambahan sari daun bayam hijau (0%, 2%, 4%, dan 6%). Analisis data menggunakan metode rancangan acak lengkap (RAL) dengan 4 taraf perlakuan dan 3 kali ulangan. Hasil terbaik penambahan sari daun bayam hijau pada pembuatan brownis kukus adalah perlakuan B2 (4%) sari daun bayam hijau, dilihat dari hasil kadar air (41,27%), kadar abu (0,59%), uji organoleptik warna 3,97 (suka), aroma 3,84 (suka), cita rasa 4,03 (suka), dan tekstur 4 (suka).